Little difference in the carbon balance of ryegrass/white clover- and plantain-dominated swards under dairy grazing - A. M. Wall; D. I. Campbell; S. Ray; J. P. Goodrich; L. A. Schipper (Nutrient Cycling in Agroecosystems, 2026)
Incorporating plantain into grazed pasture swards is proposed as an approach to reduce nitrate leaching and nitrous oxide emissions. However, consideration must be given to potential emission-swapping, such as a reduction in soil carbon (C), which can contribute to increases in atmospheric CO 2 . We compared the net ecosystem C balance (NECB) of two adjacent newly-sown paddocks (~ 3 ha each) of (i) traditional ryegrass and white clover pasture (RyWC) and (ii) a pure plantain sward, to assess whether plantain was beneficial or detrimental for the carbon balance. The NECB was calculated by combining eddy covariance (EC) measurements of CO 2 with measurements and estimates of lateral C transfers. Concurrently, regular measurements of sward composition and properties were taken. During the approximately 2.5-year experiment, the RyWC sward had an NECB of −199 g C m −2 period −1 compared with −273 g C m −2 period −1 for the plantain sward. The slightly larger loss from the plantain sward was attributed to lower excretal C returns due to differences in grazing duration (13.9 days for the RyWC paddock, and 5.9 days for the plantain paddock) during the first year of grazing. In the second year, the grazing management of the two paddocks was the same, and the NECBs were comparable. Both pasture dry matter production and CO 2 uptake were similar between the swards, although the lower C content of the plantain resulted in smaller C exports by either harvest or grazing. We conclude that small differences in NECB (and assumed soil C) between a pure plantain sward and a traditional ryegrass and white clover sward are associated with management rather than pasture species.

Despite warming temperatures, hatchery origin Chinook and coho salmon spawn earlier in the fall: a multi-decade analysis - Thomas P. Quinn; Jason Ray; Michael D. Tillotson (Hydrobiologia, 2026)

Challenges and Opportunities for Strengthening Bottom‐Tow Fisheries Sustainability - Suresh A. Sethi; Robert D. Murphy; Matthew R. Baker; Anita C. Kroska; Haraldur A. Einarsson; Owen S. Hamel; Shelton J. Harley; Pingguo He; James Ianelli; Stan Kotwicki; Robert A. McConnaughey; Chris McGonigle; et al. (Fish and Fisheries, 2026)
Bottom‐tow gear fisheries (trawls and dredges) produce ~24 million mt of harvest annually, representing a globally important animal‐sourced food system. While many are currently sustainably managed, growing concern over the potential for ecosystem impacts from bottom‐tow gears has increased pressure to improve these fisheries. We assembled an international working group of > 30 contributors, including fishing industry participants, managers, non‐governmental ocean conservation organization representatives, and scientists to synthesize obstacles to bottom‐tow fisheries sustainability and to develop expert‐based recommendations to operationalize sustainability advancements moving forward. We identified 30 key gaps impeding bottom‐towed fisheries sustainability spanning 6 core challenge areas including: seafloor disturbance, bycatch and discards, management design and implementation, fishing operations, cross‐sector conflicts, and public perception and communication. We generated 28 priority recommendations to address bottom‐tow fisheries sustainability obstacles with themes including: addressing data gaps, advancing mechanistic understanding and modelling tools, strengthening management processes, and improving knowledge sharing and communication. Cross‐disciplinary and diverse system experience among fisheries and marine ecosystem stakeholders will be critical for operationalizing bottom‐tow fisheries sustainability advancements. As the global human population approaches 10 bn in the next 30 years, ensuring sustainable wild capture fisheries is an imperative for feeding the world. Outputs from this synthesis serve as a resource for fishing and marine ecosystem stakeholders to identify key challenge areas and associated entry points for solutions‐oriented efforts to improve the sustainability of bottom‐tow fisheries.

NCBI Orthologs: Public Resource and Scalable Method for Computing High-Precision Orthologs Across Eukaryotic Genomes - Dong-Ha Oh; Alexander Astashyn; Barbara Robbertse; Nuala A. O’leary; W. Ray Anderson; Laurie Breen; Eric Cox; Olga Ermolaeva; Robert Falk; Vichet Hem; J. Bradley Holmes; Patrick Masterson; et al. (Journal of Molecular Evolution, 2025)
Orthologs are fundamental for enabling comparative genomics analyses that further our understanding of eukaryotic biology. The unprecedented increase in the availability of high-quality eukaryotic genomes necessitates scalable and accurate methods for orthology inference. The National Center for Biotechnology Information (NCBI) developed “NCBI Orthologs”, a resource and a computational pipeline designed to meet this challenge within the NCBI RefSeq framework. This system integrates protein similarity, nucleotide alignment, and microsynteny to achieve high-precision ortholog assignments across diverse eukaryotes. The pipeline leverages high-quality RefSeq annotations and processes genomes individually, ensuring scalability. Resulting ortholog data, organized into gene-level anchored sets, enables propagation of functional annotation information and facilitates comparative genomics. Critically, these data are integrated into the NCBI Gene resource, providing users with access from various entry points. The NCBI Datasets resource provides an intuitive interface to explore orthologous relationships on the web and allows bulk data download via the web, command-line tools, and an API. We detail the methodology, including anchor species selection and the decision tree used to arrive at high-confidence one-to-one orthology relationships. NCBI Orthologs is a valuable resource for facilitating functional annotation efforts and enhancing our understanding of eukaryotic gene evolution.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Simultaneous Drought and Heatwave Events During Austral Summer in Northeast Brazil - Katyelle F. S. Bezerra; Helber B. Gomes; Hakki Baltaci; Pallav Ray; Janaíına P. Nascimento; Dirceu L. Herdies; Matheus J. A. Lyra; Maria Cristina L. Silva; Fabrício D. S. Silva; Cláudio M. Santos e Silva; Heliofábio B. Gomes (International Journal of Climatology, 2025)
The simultaneous occurrence of heatwaves and droughts is becoming more frequent and intense under climate change, particularly affecting vulnerable regions like Northeast Brazil (NEB). This study presents a comprehensive assessment of these compound extremes using long‐term in situ observations and ERA5 reanalysis. Heatwaves were defined by daily temperatures exceeding the 90th percentile, and droughts by the standardised precipitation index (SPI‐1). Results reveal substantial spatio‐temporal variability in these events, with sharp increases in frequency, duration, and intensity since the early 1990s–especially in 1998, 2006 and 2015, linked to La Niña and El Niño events. Atmospheric analyses showed positive temperature anomalies at 2 m, persistent negative specific humidity at multiple pressure levels, and contrasting circulation anomalies: positive flow at 850 hPa, negative at 500 hPa, and changes in divergence and vorticity. The semiarid region of the northeast was the most affected by drought, while the northeastern coast had higher frequencies of heatwaves, with longer durations. These findings highlight the complex interactions driving compound extremes in NEB and underscore the urgent need for regional adaptation and mitigation strategies.

Offsets in tide-gauge reference levels detected by satellite altimetry: ten case studies - R. D. Ray; M. J. Widlansky; A. S. Genz; P. R. Thompson (Journal of Geodesy, 2023)
Comparing measurements of absolute sea level by satellite altimetry and relative sea level by a tide gauge can reveal errors in either measurement system. Combining the measurements can determine vertical land motion (VLM) at the tide gauge. We here discuss ten case studies in which a tide gauge has likely experienced a small ( $$\le 10$$ ≤ 10 cm), discontinuous offset in the vertical, suggesting inadvertent loss of reference-level stability. Proper interpretation of offsets is helped if independent VLM measurements from nearby geodetic stations are available. In two cases, earthquake-induced VLM cannot be ruled out, although it appears unlikely. Offsets as small as 1–2 cm can be detected when both altimeter and tide gauge successfully observe the same ocean signal. This is most likely to occur for tide gauges located on small, open-ocean islands. Tide gauges near large land masses are typically more challenging owing to inadequacies of satellite altimetry near land and to differences between coastal and open-ocean sea levels. The case studies highlight the utility of satellite altimetry for tide-gauge quality control.

Correction to: Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)

Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.

Sustainable Growing Areas for Sugarcane in Sri Lanka Under a Changing Climate - D. M. B. M. Deegala; N. S. Abeysingha; L. P. Muthuwatta; Ram L. Ray (Sugar Tech, 2022)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Applications of Advanced Geospatial Technology for Expansion of Area under Horticultural Crops in North Eastern Region of India - B. K. Handique; C. Goswami; P. Jena; F. Dutta; R. Samiam; I. Nongrum; D. Jha; P. L. N. Raju; C. R. Deka; R. Sarma; K. Sarmah; H. K. Dutta; et al. (Journal of the Indian Society of Remote Sensing, 2022)

Assimilation of Remote Sensing Data into Crop Growth Model for Yield Estimation: A Case Study from India - Murali Krishna Gumma; M. D. M. Kadiyala; Pranay Panjala; Shibendu S. Ray; Venkata Radha Akuraju; Sunil Dubey; Andrew P. Smith; Rajesh Das; Anthony M. Whitbread (Journal of the Indian Society of Remote Sensing, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Large‐scale genome sampling reveals unique immunity and metabolic adaptations in bats - Diana D. Moreno Santillán; Tanya M. Lama; Yocelyn T. Gutierrez Guerrero; Alexis M. Brown; Paul Donat; Huabin Zhao; Stephen J. Rossiter; Laurel R. Yohe; Joshua H. Potter; Emma C. Teeling; Sonja C. Vernes; Kalina T. J. Davies; et al. (Molecular Ecology, 2021)
Comprising more than 1,400 species, bats possess adaptations unique among mammals including powered flight, unexpected longevity, and extraordinary immunity. Some of the molecular mechanisms underlying these unique adaptations includes DNA repair, metabolism and immunity. However, analyses have been limited to a few divergent lineages, reducing the scope of inferences on gene family evolution across the Order Chiroptera. We conducted an exhaustive comparative genomic study of 37 bat species, one generated in this study, encompassing a large number of lineages, with a particular emphasis on multi‐gene family evolution across immune and metabolic genes. In agreement with previous analyses, we found lineage‐specific expansions of the APOBEC3 and MHC‐I gene families, and loss of the proinflammatory PYHIN gene family. We inferred more than 1,000 gene losses unique to bats, including genes involved in the regulation of inflammasome pathways such as epithelial defence receptors, the natural killer gene complex and the interferon‐gamma induced pathway. Gene set enrichment analyses revealed genes lost in bats are involved in defence response against pathogen‐associated molecular patterns and damage‐associated molecular patterns. Gene family evolution and selection analyses indicate bats have evolved fundamental functional differences compared to other mammals in both innate and adaptive immune system, with the potential to enhance antiviral immune response while dampening inflammatory signalling. In addition, metabolic genes have experienced repeated expansions related to convergent shifts to plant‐based diets. Our analyses support the hypothesis that, in tandem with flight, ancestral bats had evolved a unique set of immune adaptations whose functional implications remain to be explored.

Removal of textile dyes from water by jute stick activated carbon: process optimization and isotherm studies - R. K. Ghosh; D. P. Ray; A. Tewari; I. Das (International Journal of Environmental Science and Technology, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Correction to: Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Diversity of hepatitis C virus infection among HIV-infected people who inject drugs in India - S. S. Solomon; D. Boon; S. Saravanan; A. K. Srikrishnan; C. K. Vasudevan; P. Balakrishnan; D. Persaud; S. C. Ray; S. Mehta; S. H. Mehta (VirusDisease, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Priority Zoning of Available Micronutrients in the Soils of Agro-ecological Sub-regions of North-East India Using Geo-spatial Techniques - Siladitya Bandyopadhyay; Prasenjit Ray; Shelton Padua; S. Ramachandran; Roomesh Kumar Jena; Partha Deb Roy; D. P. Dutta; Surendra Kumar Singh; Sanjay Kumar Ray (Agricultural Research, 2018)

Transcriptomic effects of adenosine 2A receptor deletion in healthy and endotoxemic murine myocardium - Kevin J. Ashton; Melissa E. Reichelt; S. Jamal Mustafa; Bunyen Teng; Catherine Ledent; Lea M. D. Delbridge; Polly A. Hofmann; R. Ray Morrison; John P. Headrick (Purinergic Signalling, 2017)

Mineral chemistry of tourmaline from Mashak Pahar, South Purulia Shear Zone (SPSZ), eastern Indian Shield - SANTANU ACHARJEE; JYOTISANKAR RAY; PAYEL DEY; DEBAPRIYA BHATTACHARYYA; MOUSUMI BANERJEE; BASAB CHATTOPADHYAY; SHYAMAL SENGUPTA; A K BHATT; D CHOWDHURY; A K DWIVEDI; SANJOY MAHATO; ARKA RANJAN JANA; et al. (Journal of Earth System Science, 2016)

Feasibility of Singlet Analysis for Ligand Binding Assays: a Retrospective Examination of Data Generated Using the Gyrolab Platform - Tracey H. Clark; Phillip D. Yates; Allison Given Chunyk; Alison P. Joyce; Aidong Wu; Petar Pop-Damkov; Yiqun Zhang; Elizabeth A. Dreher; Laurie A. Tylaska; Jo-Ann A. Wentland; Kathleen B. Pelletier; Lindsay E. King; et al. (The AAPS Journal, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Life at the leading edge: genetic impoverishment of the spotted bass, Micropterus punctulatus, at its Western edge - J. W. Ray; M. Husemann; D. J. Lutz-Carrillo; R. S. King; P. D. Danley (Environmental Biology of Fishes, 2015)

Microbial Biomass Carbon Status in Agro-Ecological Sub Regions of Black Soils in India - Kulandaivelu Velmourougane; M. V. Venugopalan; T. Bhattacharyya; Dipak Sarkar; D. K. Pal; Apeksha Sahu; P. Chandran; S. K. Ray; Champa Mandal; K. M. Nair; Jagdish Prasad; R. S. Singh; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Developing Spectral Library of Major Plant Species of Western Himalayas Using Ground Observations - K. R. Manjunath; Amit Kumar; Mehra Meenakshi; R. Renu; S. K. Uniyal; R. D. Singh; P. S. Ahuja; S. S. Ray; Sushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2014)

Urease Activity in Various Agro-ecological Sub-regions of Black Soil Regions of India - Kulandaivelu Velmourougane; M. V. Venugopalan; T. Bhattacharyya; Dipak Sarkar; D. K. Pal; Apeksha Sahu; P. Chandran; S. K. Ray; Champa Mandal; K. M. Nair; Jagdish Prasad; R. S. Singh; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

Acaricide resistance status in Indian isolates of Hyalomma anatolicum - K. P. Shyma; Sachin Kumar; Anil Kumar Sharma; D. D. Ray; S. Ghosh (Experimental and Applied Acarology, 2012)

Comparison of Two Data Smoothing Techniques for Vegetation Spectra Derived From EO-1 Hyperion - Anshu Miglani; Shibendu S. Ray; D. P. Vashishta; Jai Singh Parihar (Journal of the Indian Society of Remote Sensing, 2011)

Assessment of the Jason-2 Extension to the TOPEX/Poseidon, Jason-1 Sea-Surface Height Time Series for Global Mean Sea Level Monitoring - B. D. Beckley; N. P. Zelensky; S. A. Holmes; F. G. Lemoine; R. D. Ray; G. T. Mitchum; S. D. Desai; S. T. Brown (Marine Geodesy, 2010)

Shift in detrital sedimentation in the eastern Bay of Bengal during the late Quaternary - C. Prakash Babu; J. N. Pattan; K. Dutta; N. Basavaiah; G. V. Ravi Prasad; D. K. Ray; P. Govil (Journal of Earth System Science, 2010)

Male-Produced Aggregation Pheromone of the Cerambycid Beetle Rosalia funebris - Ann M. Ray; Jocelyn G. Millar; J. Steven McElfresh; Ian P. Swift; James D. Barbour; Lawrence M. Hanks (Journal of Chemical Ecology, 2009)

Acetylcholinesterase activities in marine snail (Cronia contracta) as a biomarker of neurotoxic contaminants along the Goa coast, West coast of India - D. Gaitonde; A. Sarkar; S. Kaisary; C. D. Silva; C. Dias; D. P. Rao; D. Ray; R. Nagarajan; S. N. De Sousa; Subhodeep Sarker; D. Patill (Ecotoxicology, 2006)

Light-regulated overexpression of an Arabidopsis phytochrome A gene in rice alters plant architecture and increases grain yield - Ajay K. Garg; Ruairidh J. H. Sawers; Haiyang Wang; Ju-Kon Kim; Joseph M. Walker; Thomas P. Brutnell; Mandayam V. Parthasarathy; Richard D. Vierstra; Ray J. Wu (Planta, 2006)

Inhibition of Amazon Deforestation and Fire by Parks and Indigenous Lands - D. NEPSTAD; S. SCHWARTZMAN; B. BAMBERGER; M. SANTILLI; D. RAY; P. SCHLESINGER; P. LEFEBVRE; A. ALENCAR; E. PRINZ; GREG FISKE; ALICIA ROLLA (Conservation Biology, 2006)
Conservation scientists generally agree that many types of protected areas will be needed to protect tropical forests. But little is known of the comparative performance of inhabited and uninhabited reserves in slowing the most extreme form of forest disturbance: conversion to agriculture. We used satellite‐based maps of land cover and fire occurrence in the Brazilian Amazon to compare the performance of large (>10,000 ha) uninhabited (parks) and inhabited (indigenous lands, extractive reserves, and national forests) reserves. Reserves significantly reduced both deforestation and fire. Deforestation was 1.7 (extractive reserves) to 20 (parks) times higher along the outside versus the inside of the reserve perimeters and fire occurrence was 4 (indigenous lands) to 9 (national forests) times higher. No strong difference in the inhibition of deforestation (p= 0.11) or fire (p= 0.34) was found between parks and indigenous lands. However, uninhabited reserves tended to be located away from areas of high deforestation and burning rates. In contrast, indigenous lands were often created in response to frontier expansion, and many prevented deforestation completely despite high rates of deforestation along their boundaries. The inhibitory effect of indigenous lands on deforestation was strong after centuries of contact with the national society and was not correlated with indigenous population density. Indigenous lands occupy one‐fifth of the Brazilian Amazon—five times the area under protection in parks—and are currently the most important barrier to Amazon deforestation. As the protected‐area network expands from 36% to 41% of the Brazilian Amazon over the coming years, the greatest challenge will be successful reserve implementation in high‐risk areas of frontier expansion as indigenous lands are strengthened. This success will depend on a broad base of political support.

Molecular pathogenesis of Wilson disease: haplotype analysis, detection of prevalent mutations and genotype–phenotype correlation in Indian patients - A. Gupta; D. Aikath; R. Neogi; S. Datta; K. Basu; B. Maity; R. Trivedi; J. Ray; S. K. Das; P. K. Gangopadhyay; K. Ray (Human Genetics, 2005)

High iridium concentration of alkaline rocks of Deccan and implications to K/T boundary - P. N. Shukla; N. Bhandari; Anirban Das; A. D. Shukla; J. S. Ray (Journal of Earth System Science, 2001)

Integrated commodity management methods with ca and/or fumigation - S. Prabhakaran; S. Ray; B. M. Schneider; R. E. Williams; P. Flinn; T. Phillips; D. Hagstrum; F. Arthur; J. Throne; R. N. Emery; R. A. Tassone; E. Kostas; et al. (Phytoparasitica, 2001)

Physico-Chemical Quality of Drinking Water in Rohtas District of Bihar - D. Ray; R. Ravindar Rao; A. V. Bhoi; A. K. Biswas; A. K. Ganguly; P. B. Sanyal (Environmental Monitoring and Assessment, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Rabies viruses infect primary cultures of murine, feline, and human microglia and astrocytes - N. B. Ray; C. Power; W. P. Lynch; L. C. Ewalt; D. L. Lodmell (Archives of Virology, 1997)

Genetic differentiation of populations of the common intertidal nemerteans Lineus ruber and Lineus viridis (Nemertea, Anopla) - Alex D. Rogers; John P. Thorpe; Ray Gibson; Jon L. Norenburg (Hydrobiologia, 1997)

Effect of methyl isocyanate (MIC) on rat erythrocytes - Deepa Agrawal; G. S. D. Gupta; J. S. Shukla; K. K. Dutta; P. K. Ray (Archives of Toxicology, 1990)

A study of nerve conduction velocity, late responses and neuromuscular synapse functions in organophosphate workers in India - U. K. Misra; D. Nag; W. A. Khan; P. K. Ray (Archives of Toxicology, 1988)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)